Multichannel Data Aquisition System for Monitoring Supercapacitor Module And Cells - Nirwan Syarif; Assaidah Assaidah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexThe monitoring system is needed to observe changes in the voltage of supercapacitor module and cells so that their performance can be assessed. A multichannel data acquisition system was needed to implement because a module of supercapacitor consists of several individual cells. The system can be implemented in a computer program using data acquisition board and computer programming. The computer program acts as computer and user interface was created by using Labview symbolic programming software, while the data acquisition board was Labjack. The test showed that the monitoring system can receive eight channel of input signal (voltage) of the module and cells simultaneously. The voltage of the module which has a wider range, 0-20 volts, rather than the normal input, 0 to 2.44 volts, can be overcome by adding a voltage divider circuit.